Carrier Mobilities in Amorphous Organic Semiconductor Films Prepared at Various Film Formation Processes. Issue 19 (12th August 2021) - Miyashige, Katsuya; Morimoto, Masahiro; Naka, Shigeki
Abstract : The hole mobility of an organic semiconductor film that consists of N, N '‐di (1‐naphthyl)‐ N, N '‐diphenyl‐benzidine (α‐NPD) is evaluated at various film formation processes, such as vacuum deposition and capillary injection. The mobility varies with the film formation process. From the temperature dependence of mobility, the Poole−Frenkel model and disorder model are discussed. From the analysis based on the Poole−Frenkel model, activation energies of the vacuum‐deposited film, the slowly cooled‐melted film, and the rapidly cooled‐melted film are 0.28, 0.20, and 0.40 eV, respectively. This result suggests that organic semiconductor thin films formed by different film formation methods have different molecular aggregation states. Abstract : Hole mobility and the temperature dependence of amorphous organic semiconductor material that consists of N, N '‐di (1‐naphthyl)‐ N, N '‐diphenyl‐benzidine are evaluated by time‐of‐flight method. Three types of samples are prepared at various film formation processes, such as vacuum‐deposited film, slowly cooled‐melted film, and rapidly cooled‐melted film. There is a correlation between activation energy and film formation process.